Analisis Beberapa Faktor yang Mempengaruhi Ekspor Kerajinan Ukiran Kayu Indonesia ke Amerika Serikat Tahun 1996-2012 - Widhi Ari, Ni Nyoman; Meydianawathi, Luh Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 6, Juni 2014 (pp.227 - 281), 2014)
Indonesia as a developing country, can not be separated from the activities of international trade in the form of exports and imports. Exports tend to done to increase the national income, one of which exports of wood carving craft, which belong to the type of industry in the non-oil sector. The study, entitled "Analysis of Factors Affecting the Export of Wood Carving Craft Indonesia to the United States in 1996-2012" using secondary data obtained from the web UN Comtrade, BPS, BKPM, and BI. The study aims to determine whether there are significant simultaneously or partially between the United States GDP, world inflation, investment, and the dollar exchange rate to wards the Indonesian wood carving handicraft exports to the United States. The results of data analysis using multiple linear regression analysis showed 86.2 percent of United States GDP variable, inflation world, Indonesia's investment, and United States dollar exchange rate affect exports of Indonesian wood carving craft to the United States in 1996-2012. Partially United States GDP variable is positive and significant effect, variable inflation world, Indonesia's investment and the dollar exchange rate and a significant negative effect.